2010
DOI: 10.1007/s10840-010-9481-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic characteristics and radiofrequency ablation of focal atrial tachycardia arising from non-coronary sinuses of Valsalva in the aorta

Abstract: This study demonstrated that mapping and ablation of focal AT arising from NCC is safe and effective. When earliest activation was recorded in the proximal electrode of the His-bundle catheter, but radiofrequency ablation in this region cannot successfully eliminated the tachycardia, the AT should be considered to arise from NCC especially when P-wave morphology was initially negative with a late positive component in right precordial leads, upright or biphasic in inferior leads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…An aortic cusp (AC) is one of embryologic raphe structures and an excellent target for catheter ablation of some VTs originating from the left ventricular outflow tract (LVOT) because it allows good contact and stable position of the catheter [7,8]. However, radiofrequency catheter ablation (RFCA) of supraventricular tachyarrhythmias (SVTs) is rarely performed at the AC in patients with atrial tachycardia (AT) [9,10] or atrioventricular reciprocating tachycardia (AVRT) [11][12][13][14][15]. Recently, it was reported that aortographically determined anatomical position of AC and their electrogram pattern lead to safe and effective catheter ablation [16].…”
Section: Introductionmentioning
confidence: 99%
“…An aortic cusp (AC) is one of embryologic raphe structures and an excellent target for catheter ablation of some VTs originating from the left ventricular outflow tract (LVOT) because it allows good contact and stable position of the catheter [7,8]. However, radiofrequency catheter ablation (RFCA) of supraventricular tachyarrhythmias (SVTs) is rarely performed at the AC in patients with atrial tachycardia (AT) [9,10] or atrioventricular reciprocating tachycardia (AVRT) [11][12][13][14][15]. Recently, it was reported that aortographically determined anatomical position of AC and their electrogram pattern lead to safe and effective catheter ablation [16].…”
Section: Introductionmentioning
confidence: 99%
“…Since its original clinical description, 10 over 20 studies of ATP‐sensitive AT‐HB have been published worldwide in peer‐reviewed, medical journals 32–51 . In most of these studies, this AT was diagnosed in accordance with the original report 10 .…”
Section: Discussionmentioning
confidence: 87%
“…Большинство других отчетов описывают аналогичную стратегию [11,14,23]. S. Das et al предлагают переходить к картированию некоронарной створки только в том случае, если картирование ПП обнаружит раннюю активацию в парагисиальной области.…”
Section: Discussionunclassified
“…В последнее время у больных, демонстрирующих во время предсердного картирования наиболее раннюю активацию в зоне АВ-узла, с успехом стала применяться катетерная аблация из синусов Вальсальвы, особенно центрально расположенного некоронарного синуса Вальсальвы (НСВ), где радиочастотные (РЧ) воздействия более безопасны [10,11].…”
Section: Introductionunclassified